Growth and genome-based insights of Fe(III) reduction of the high-temperature and NaCl-tolerant Shewanella xiamenensis from Changqing oilfield of China - Yang, Jiani; Zhao, Dan; Liu, Tao; Zhang, Shuang; Wang, Weidong; Yan, Lei; Gu, Ji-Dong (Frontiers in Microbiology, 2022)
A facultative anaerobe bacterium Shewanella xiamenensis CQ-Y1 was isolated from the wastewater of Changqing oilfield in Shaanxi Province of China. Its complete genome was a circular chromosome of 4,710,887 bp with a GC content of 46.50% and 4,110 CDSs genes, 86 tRNAs and 26 rRNAs. Genomic analysis revealed genes encoding for Na+/H+ antiporter, K+/Cl− transporter, heat shock protein associated with NaCl and high-temperature resistance. The presence of genes related to flavin, Cytochrome c, siderophore, and other related proteins supported Fe(III) reduction. The tolerance test and Fe(III) reduction experiments of CQ-Y1 were carried out. The results showed that CQ-Y1 could survive at 10% NaCl (w/v) and 45 oC, and temperature showed more pronounced effects than NaCl concentration on the bacterial growth. The maximum Fe(III) reduction ratio of CQ-Y1 reached 70.1% at 30 oC without NaCl, and the reduction reaction remained active at 40°C with 3% NaCl (w/v). NaCl concentration was more effective than temperature on microbial Fe(III) reduction. SEM and XRD showed that the reduction products under high temperature and high NaCl conditions were characterized as Fe3(PO4)2, FeCl2 and Fe(OH)2. Accordingly, a Fe(III) reduction mechanism of CQ-Y1 mediated by Cytochrome c and flavin was hypothesised. These findings could provide information for a better understanding of the origin and evolution of genomic and metabolic diversity of S. xiamenensis.